Estimating total glomerular number in human kidneys with a physical disector/fractionator combination - Johnson, Kelli J (Image analysis and stereology, 2000)
End-stage renal disease (ESRD) has emerged as a major health issue for Australian Aborigines. This phenomenon is paralleled in other populations thathave adopted a Westernised lifestyle, including African Americans. It has been suggested that abnormal glomerular hypertrophy (glomerulomegaly) is an important predisposing factor for ESRD. The pathogenesis of glomerulomegaly remains unknown. It may represent a compensatory hypertrophic response to decreased nephron endowment during fetal development. Alternatively, glomerulomegaly may represent an abnormal haemodynamic/metabolic response to repeated infections, including renal infections during postnatal life. Since glomerular number and size are important issues associated with ESRD, an optimum quantitative method is required for estimating these parameters in human kidneys. The total number of glomeruli in the normal human kidney appears to vary by a factor of three or more, ranging from approximately 300,000 to more than 1 million. Recently, unbiased stereological methods for estimating total glomerular number in kidneys have been developed. The generalaim of the present study was to evaluate (in terms of precision and efficiency) a stereological method for estimating total glomerular number in human kidneys; the physical disector/fractionator combination. This method provided consistent estimates of total glomerular number. Estimates of total glomerular number obtained for four human kidneys ranged from 364,161 to 586,094 (coefficients of variation 9.2% to 20.0%). Mean glomerular volume for the four kidneys ranged from 6.04 to 10.32 micro m3 x 106. These results indicate that this method is a precise and consistent method for estimating total glomerular number in human kidneys. (Abstract truncated at 2000 characters)
Keywords: Kidney glomerulus; ledvice; Anatomy and histology; histologija; stereologija; Kidney failure, chronic; Histological techniques; Image processing, computer-assisted